CLASSICAL ANTIQUITY AS A FOUNDATION OF MODERN LITERARY THOUGHT: CLASSICAL IMAGES AND MOTIFS IN THE WORKS OF ALBERT CAMUS AND EASTERN MODERN PROSE (Multidisciplinary Journal of Science and Technology, 2026)
This article examines classical antiquity's influence on modern literature, analyzing how Albert Camus and Eastern writers reinterpret Greek myths and classical motifs to address contemporary existential and philosophical questions.